Cystic epithelial lining seen around a dental implant: A case report of a rare finding - Yazad Gandhi; Neel Bhatavadekar (Elsevier, 2020)
Dental implants have been successfully used for over 30 years, with a low complication rate. Peri-implant pathologies have recently seen an increase in incidence.This case report elucidates a rare case implant failure that occurred shortly after prosthetic loading, where the clinical signs mimicked peri-implant disease and attending bone loss, but the final histological report confirmed presence of a cystic lining around the implant. The manuscript also emphasizes the possible causes and management of such complications.To the best of our knowledge, this represents one of the first publication of an evident peri-implant cystic lining in a case exhibiting no radiographic evidence of the same.